Positive Welfare in Science and Society: Differences, Similarities and Synergies - Vigors, Belinda; Sandøe, Peter; Lawrence, Alistair B. (Frontiers in Animal Science, 2021)
Societal and scientific perspectives of animal welfare have an interconnected history. However, they have also, somewhat, evolved separately with scientific perspectives often focusing on specific aspects or indicators of animal welfare and societal perspectives typically taking a broader and more ethically oriented view of welfare. In this conceptual paper, we examine the similarities and differences between scientific and societal perspectives of positive welfare and examine what they may mean for future discussions of animal welfare considered as a whole. Reviewing published studies in the field we find that (UK and Republic of Ireland) farmers and (UK) members of the public (i.e., society) typically consider both negatives (i.e., minimising harms) and positives (i.e., promoting positive experiences) within the envelope of positive welfare and prioritise welfare needs according to the specific context or situation an animal is in. However, little consideration of a whole life perspective (e.g., the balance of positive and negative experiences across an animal's lifetime) is evident in these societal perspectives. We highlight how addressing these disparities, by simultaneously considering scientific and societal perspectives of positive welfare, provides an opportunity to more fully incorporate positive welfare within a comprehensive understanding of animal welfare. We suggest that a consideration of both scientific and societal perspectives points to an approach to welfare which accounts for both positive and negative experiences, prioritises them (e.g., by seeing positive experiences as dependent on basic animal needs being fulfilled), and considers the balance of positives and negatives over the lifetime of the animals. We expand on this view and conclude with its potential implications for future development of how to understand and assess animal welfare.